Pathology and pain, disease and disability: The burdens of the body in the Book of Job peering through a psychoanalytic prism - Zwan, Pieter van der (HTS teologiese studies, 2022)
Not only trauma, mourning and disease, but also disability has been recognised in the Book of Job in which the body plays an exceptional role. The protagonist is suffering physically, psychically and spiritually. Although the word, חלה [be sick, ill], never occurs in the book, his body is portrayed negatively being afflicted by some unknown illness, which would probably exclude him from the community described in Leviticus 13–14. While חָרֵשׁ [be silent] occurs several times in the book, it never has the alternative meaning of deaf. Yet, his explicit empathy and sacrificial charity לַעִוֵּר [for the blind] and לַפִּסֵּחַ [for the lame] in 29:15 resonate with his own plight and undermine the possible discriminatory restrictions of like disabled in Leviticus 21:18. In this way, the Book of Job has a transgressive and yet liberating subtext, subverting the idealised body of his status quo. This subtle and veiled critique by the protagonist and therefore the book can be interpreted from a psychoanalytic perspective on physical disability and illness, where the symptoms and alleged imperfections of the body quietly cry out against social and cultural injustice of which they are the projections and mirrors when the context has silenced a concern for the body because of a lack of compassion as it is in the situation of Job.Contribution: The intersection and cross-fertilisation of Biblical Studies, Disability Studies and psychoanalytic theory as interdisciplinary approach widens the horizons and deepens the insight of all three research fields, hopefully for the benefit of those who suffer from their bodies, their psyches and their societies.